Gender analysis in grain maize value chain in Northern and Central Benin - Adetonah, S.; Coulibaly, O.; Satoguina, H.; Sangare, A.; Dossavi-yovo, N.H. (2016)
Maize is one of the most important food crops in the world and, together with rice and wheat, provides at least 30% of the food calories to more than 4.5 billion people in 94 developing countries. (Bekele Shiferawet al, 2011). It is produced across Benin and mainly women and young people are involved in the maize grain value chain. Study aim to carry out a gender analysis in the maize grain value chain in northern and central Benin. Specifically it analyze the division of labor according to gender in the grain maize value chain, identify the factors that influence access to and control of resources and measure the distribution of profits from the commercialization activities. Data have been collected at random in a stratified method including 90 producers, 33 processors and 33 corn traders. The Harvard analytic framework of Harward, the descriptive statistic and the binominal logitpatterens have been used for the analysis In terms of resource accessibility, the results showed that men have more access and control the resources in both areas than women with limited access to credit, training, land and information in the chain. Moreover, the logistic regression results noted that socio-economic factors such as level of education, accessibility to credits and equipment positively affect the control of resources by women.